1999
DOI: 10.1002/1529-0131(199909)42:9<2007::aid-anr30>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Mixed cryoglobulinemia secondary to visceral Leishmaniasis

Abstract: We describe a case of type II mixed cryoglobulinemia, with monoclonal IgM rheumatoid factor, associated with visceral leishmaniasis caused by Leishmania infantum. Involvement of Leishmania antigen(s) in the formation of cryoprecipitable immune complexes was suggested by the fact that cryoglobulinemic vasculitis subsided after antiparasite therapy and that anti-Leishmania antibodies, as well as rheumatoid factor, were enriched in the cryoprecipitate. We observed 2 additional patients with visceral leishmaniasis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 12 publications
0
23
0
Order By: Relevance
“…2,3 Visceral leishmaniasis has also been implicated as a cause of cryoglobulinemia. 5 These manifestations of visceral leishmaniasis have been proposed to be a result of chronic antigenic stimulation that occurs in these patients. 4 Monoclonal gammopathy associated with visceral leishmaniasis should be distinguished from monoclonal gammopathy of undetermined significance (MGUS).…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Visceral leishmaniasis has also been implicated as a cause of cryoglobulinemia. 5 These manifestations of visceral leishmaniasis have been proposed to be a result of chronic antigenic stimulation that occurs in these patients. 4 Monoclonal gammopathy associated with visceral leishmaniasis should be distinguished from monoclonal gammopathy of undetermined significance (MGUS).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that high levels of parasite-specific IgG are generated during leishmaniasis (46,47). This is especially true with human visceral leishmaniasis in which rheumatoid factor (48 -50) and parasite-specific IgG levels are high (27)(28)(29)(30)(31)(32), making it more likely that amastigotes derived from lesions would be opsonized with host IgG. Our model would predict that disease exacerbation caused by immune complexes would only occur late in disease, after parasite-specific IgG was generated.…”
Section: Discussionmentioning
confidence: 99%
“…IgG Abs to Leishmania are prominent in human visceral leishmaniasis, and they are also produced in BALB/c mice during Leishmania infection (27)(28)(29)(30)(31)(32). The levels of IgG increase as disease progresses and parasites disseminate.…”
Section: Il-10 Reduces Ag Presentation and Either Inhibits Or Biases mentioning
confidence: 99%
“…infantum co-exist. Although the burden of VL in North Africa is mainly in children aged between 1 and 4 years of age, VL can present clinical and laboratory autoimmune manifestations including arthralgia, cutaneous vasculitis, increased titers of rheumatoid factor (RF) and antinuclear antibodies (ANA) [27][28][29]. VL patients may initially be misdiagnosed as having an autoimmune disease such as SLE or autoimmune hepatitis, leading to the possibility that they could be treated with immunosuppressive drugs with fatal consequences [30].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we assessed crude mixtures of Leishmania histones (CLH) and the related single recombinant histones rH2A, rH2B and rH4 derived from L. infantum [27].…”
Section: Discussionmentioning
confidence: 99%